Relating fitness to long‐term environmental variations in natura - Pascal Milesi; Thomas Lenormand; Christophe Lagneau; Mylène Weill; Pierrick Labbé (Molecular Ecology, 2016)
Quantifying links between ecological processes and adaptation dynamics in natura remains a crucial challenge. Many studies have documented the strength, form and direction of selection, and its variations in space and time, but only a few managed to link these variations to their proximal causes. This step is, however, crucial, if we are to understand how the variation in selective pressure affects adaptive allele dynamics in natural settings. We used data from a long‐term survey (about 30 years) monitoring the adaptation to insecticides of Culex pipiens mosquitoes in Montpellier area (France), focusing on three resistance alleles of the Ester locus. We used a population genetics model taking temporal and spatial variations in selective pressure into account, to assess the quantitative relationships between variations in the proximal agent of selection (amounts of insecticide sprayed) and the fitness of resistance alleles. The response to variations in selective pressure was fast, and the alleles displayed different fitness‐to‐environment relationships: the analyses revealed that even slight changes in insecticide doses could induce changes in the strength and direction of selection, thus changing the fitness ranking of the adaptive alleles. They also revealed that selective pressures other than the insecticides used for mosquito control affected the resistance allele dynamics. These fitness‐to‐environment relationships, fast responses and continuous evolution limit our ability to predict the outcome of adaptive allele dynamics in a changing environment, but they clearly contribute to the maintenance of polymorphism in natural populations. Our study also emphasizes the necessity of long‐term surveys in evolutionary ecology.

Identification of Outer Membrane Proteins Altered in Response to UVC-Radiation in Vibrio parahaemolyticus and Vibrio alginolyticus - Fethi Ben Abdallah; Rihab Lagha; Ali Ellafi; Abdelkader Namane; Jean-Claude Rousselle; Pascal Lenormand; Héla Kallel (Indian Journal of Microbiology, 2012)

Regulatory role of UvrY in adaptation of Photorhabdus luminescens growth inside the insect - Evelyne Krin; Sylviane Derzelle; Karine Bedard; Minou Adib‐Conquy; Evelyne Turlin; Pascal Lenormand; Marie‐Francoise Hullo; Isabelle Bonne; Nesrine Chakroun; Celine Lacroix; Antoine Danchin (Environmental Microbiology, 2008)
Summary We report global expression profiling of a uvrY‐ deficient mutant of Photorhabdus luminescens . We found that the regulator moiety of the two‐component regulatory system BarA/UvrY regulated more than 500 target genes coding for functions involved in the synthesis of major compartments and metabolic pathways of the cell. This regulation appeared to be in part indirect as UvrY affected the expression of several regulators. Indeed, the flagellum biosynthesis transcription activator FlhC and the flagella regulon were induced in the absence of UvrY, leading to a hyperflagellated phenotype and an increase in motility and biofilm formation. Two major regulatory systems were also altered: the type 2 quorum‐sensing inducer AI‐2 was activated by UvrY, and the CsrA regulator function appeared to be repressed by the increase of the small‐untranslated RNA csrB , the CsrA activity inhibitor TldD and the chaperonin GroESL. Both through and independently of these systems, UvrY regulated oxidative stress resistance; bioluminescence; iron, sugar and peptide transport; proteases; polyketide synthesis enzymes and nucleobases recycling, related to insect degradation and assimilation by bacteria. As a consequence, the uvrY ‐deficient strain exhibited a decreased killing of insect cells and a reduced growth on insect cells culture, suggesting a UvrY role in the adaptation of P. luminescens inside the insect.